The Influence of Ship Engine Noise Levels on Work Stress Levels of Ship Technicians - Nawawi, Cholis Imam; Widodo, Agus; Dewi, Astri Kustina; Amala, Riza Nur (PT ARRUS Intelektual Indonesia, 2024)
Unnoticed high-intensity noise causes serious impacts on people ABK. Measuring noise levels in engine rooms on ships. Provide a solution how reduce noise and impact noise. The research aims to determine the level noise in the engine room. Excessive noise can cause an impact on employee health. Formulation of the problem in. This research is the relationship between noise intensity and stress levels worked as a ship technician The research was carried out using a sound level meter, measurement tool carried out in the engine room and measurements work stress level